The Effects of Replacing Incarceration with Electronic Monitoring on Crime, Mortality, and Labor Market Exclusion - Al Weswasi, Enes (Journal of quantitative criminology, 2025)
ObjectiveIn recent decades, electronic monitoring (EM) has increasingly come to be used as an alternative to incarceration. However, EM’s long-term effects on offenders remain unclear, especially with regard to non-recidivism-related outcomes and reincarceration risks. This study focuses on the long-term impact of EM on recidivism, mortality, and labor market exclusion.MethodThe study utilizes administrative data, and focuses on a Swedish EM reform as a natural experiment with a difference-in-difference approach. The reform enabled offenders sentenced to up to six months’ imprisonment to serve their sentences under EM instead of in prison.ResultsThe findings show that introducing the possibility to transform a prison stay to EM at home reduced 10-year reconviction and reincarceration rates. They also show that the reform had long-lasting decreasing effect on the likelihood of not being in education, employment, or training (NEET). The reform had, however, no effect on all-cause mortality or death by suicide. Heterogeneity analyses show that the effects are primarily driven by individuals who had a more stable labor market attachment prior to being sentenced to prison, which suggests that EM helps offenders sustain regular employment and that it decreases the criminogenic impact of labor market detachment.ConclusionIn addition to reducing the costs associated with recidivism and labor market exclusion, the reduced incarceration costs associated with transforming prison sentences to EM indicate that EM has the potential to produce net savings from a societal perspective.